Dinamika Kepribadian Tokoh Eikichi Onizuka dalam Drama Great Teacher Onizuka (2012): Psikoanalisis Sigmund Freud - Bashori, Iwan Fajar; Soelistyowati, Diah (KIRYOKU, 2026)
This study aims to reveal how the personality structure of the character Eikichi Onizuka is portrayed in the drama Great Teacher Onizuka (2012). The drama depicts Onizuka as a teacher and former motorcycle gang member who employs unconventional approaches in guiding his students. This research adopts Sigmund Freud’s psychoanalytic framework of personality structure and dynamics, which encompasses the functions of the id, ego, and superego, along with psychological processes such as inner conflict and defense mechanisms that shape individual behavior. The study employs a descriptive qualitative method, with data consisting of dialogue and visual material in the form of screenshots taken from Great Teacher Onizuka. Data were collected through attentive viewing and systematic note-taking, producing 8 findings that illustrate the structure and dynamics of the character’s personality. The results demonstrate that Onizuka’s behavior emerges from the dynamic interaction between the spontaneous impulses of the id, the ego’s regulation of reality, and the moral considerations governed by the superego. Within this dynamic, the ego functions as the dominant element that balances instinctual impulses and moral demands.